The Challenges of Drone ApplicationÂ in the Construction Industry - Yahya, Mohd Yamani; Shun, Wong Pao; Md Yassin, Azlina; Omar, Roshartini (Journal of Technology Management and Business, 2021)
Drone technology is currently being used in many areas, and the increasing prevalence of drones is evident in all areas. Drones were first used for military purposes and now they have become an important part of military actions. In recent years, drone technology has become widespread in various industries including journalism, filmmaking, aerial photography, shipping, delivery. However, drone technology is still in its infancy and has not had a significant impact on the construction industry in Malaysia. Therefore, the study’s objective was to assess the challenges preventing the application of drone technology in the Malaysian construction industry. The methodology used for this research was qualitative, which is data collection through interviews with three drone experts. The respondents in this research were directors of construction companies that use unmanned aerial vehicles for their operations. The findings showed that drones faced the challenges of unfamiliarity, lack of knowledge, reticence to adopt new technologies, privacy issues, and security issues. These challenges faced by drone technology will not prevent its application in the Malaysian construction industry. However, Government support is important in promoting the use of drone technology and raising people’s awareness of drone technology in the construction industry.